MODERNISASI PARTAI POLITIK DI TINGKAT LOKAL (Studi Kasus Partai Demokrat Kabupaten Semarang, Kota Salatiga, dan Kabupaten Purworejo) - Iwan Hardi Saputro (Program Magister Ilmu Politik, Universitas Diponegoro, 2016)
The study on the modernization of the Democratic Party interesting to study. This is because in the process of modernization of the Democratic Party suffered a variety of challenges and obstacles. In addition to corruption, challenges and constraints experienced in the Democratic Party to modernization is the emergence of internal conflicts. Based on the short description, this study examines the political modernization of the Democratic Party at the local level, particularly in the district of Semarang, Salatiga, and Purworejo. This research method using descriptive research design with a qualitative approach that is supported by a simple quantitative approach. The results of this study indicate that in the context of the implementation of the indicators of modern political parties, transparency in financial management reporting party associated with the use of party funds and others is quite good. However, for some sub indicators, particularly in conflict resolution mechanisms are still difficulties and needs to be addressed. Therefore, to support the modernization of the Democratic Party could solve the problem, including internal conflict through a mechanism that has been set in the AD / ART. Keywords: Modernization, Political Parties, Local